PENGEMBANGAN POTENSI DESA WISATA DALAM RANGKA PENINGKATAN EKONOMI PERDESAAN DI KABUPATEN WONOGIRI - Lilyk Eka Suranny (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
Tourist attraction is something that can encourage tourists to visit a tourist destination. The tourism village of Conto is one of the tourist villages. The purpose of this research is to identify tourism potential in the village of Conto and formulate strategic steps in the context of developing the tourism village of Conto. Data collection was carried out through in-depth interviews, document study and observation. The data analysis used a qualitative descriptive analysis of the tourism potential in the village of Conto, the support of the village government in developing tourism in the village of Conto and strategic steps in developing the tourism village of Conto. The results showed that the tourism potential that could be developed in the village of Conto consisted of natural tourism potential, agro-tourism and cultural potential. Development plans for the tourism village of the sample include: attraction development through the creation of tour packages that are packaged in an attractive and structured manner; accessibility development through the provision of adequate infrastructure facilities; amenitas development through increasing the carrying capacity of tourism supporting facilities, and developing tourism activities both from the community and from the management of the Conto Tourism Village to realize sustainable tourism development.